Assessing the Effectiveness of Students' Online Learning amid the COVID-19 Epidemic - Thi Mai Oanh, Lu; Thuy, Nguyen Thi Nhu (VNU Journal of Science: Education Research, 2020)
This paper analyzes the effectiveness of students' online learning in the context of the COVID-19 epidemic based on the online survey data of 225 Ho Chi Minh City University of Technology and Education’s students with males accounting for 74.7% and females, 25.3%. The results show that the online teaching somewhat met the students’ learning expectations, bringing certain convenience in saving travel time, allowing more time for studying learning materials, among others. However, the online learning shows that there were still a number of difficulties related to the means of learning, learning space and insufficient interaction, which led to lower effectiveness than traditional learning. Therefore, the research results are expected to help provide a more objective view on the current situation of online learning in the context of the COVID-19 epidemic.